Determinantes da adoção do hedge accounting pelos bancos brasileiros - Dantas, José Alves (2023)
This study aimed to identify the determining factors for adopting hedge accounting by Brazilian banks that publish financial statements in IFRS. In order to carry out the tests, the IFRS financial statements of 41 banks were examined from 2015 to 2020. The results of the empirical tests revealed that the adoption of hedge accounting is positively related to the fact that banks have a controlling capital of private nature, be publicly traded (listed on B3), and have investments abroad in the form of facilities or subsidiaries; and the level of participation of customer loans and bonds and securities portfolios in the entities' equity structure. The tests also showed that the size of the banks, the fact that they are listed in B3's governance levels, and the level of profitability of the entities do not help to explain the adoption of hedge accounting by Brazilian banks. The results make it possible to identify patterns in the financial institutions that most adopt hedge accounting and enable economic agents to understand the accounting choices practiced by these entities, considering their relevance for the financial industry - especially regarding the need for risk and capital management in companies in this segment. Additionally, the findings fill a gap in the literature regarding the financial segment, identifying factors that act as incentives for adopting hedge accounting – an accounting practice compatible with risk management by Brazilian banks.